2021
DOI: 10.1099/ijsem.0.004932
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacter rhinopitheci sp. nov., a bacterium isolated from the faeces of Rhinopithecus bieti

Abstract: A novel Gram-stain-negative strain, WQ 117T, isolated from the faeces of Rhinopithecus bieti collected at Yunnan Snub-nosed Monkey National Park, Yunnan province, PR China, was subjected to a polyphasic taxonomic study. The results of phylogenetic analysis based on 16S rRNA gene sequences indicated that the isolate represented a member of the genus Faecalibacter , sharing 97.64 % sequence similarity with the type strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…From the obtained pure cultures, it was found that the similarities of 16S rRNA gene sequences of 20 strains were less than or equal to 98.7% when compared to those of their most related strains (one of the criteria of new species classification) 67 , indicating that these strains were potential new taxa (Table S7 ). Among them, WQ 047 and WQ 117 have been identified as new taxon and validly published 24 , 25 , and renamed as Sphingobacterium Rhinopitheci WQ 047 T and Faecalibacter Rhinopitheci WQ117 T , respectively. Among the remaining species, WQ 2009 T has the lowest sequence similarity with its most similar species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the obtained pure cultures, it was found that the similarities of 16S rRNA gene sequences of 20 strains were less than or equal to 98.7% when compared to those of their most related strains (one of the criteria of new species classification) 67 , indicating that these strains were potential new taxa (Table S7 ). Among them, WQ 047 and WQ 117 have been identified as new taxon and validly published 24 , 25 , and renamed as Sphingobacterium Rhinopitheci WQ 047 T and Faecalibacter Rhinopitheci WQ117 T , respectively. Among the remaining species, WQ 2009 T has the lowest sequence similarity with its most similar species.…”
Section: Resultsmentioning
confidence: 99%
“…Through serial dilutions with 0.1% sterilized Na 4 P 2 O 7 , samples were spread on Columbia Agar plates (Hopebio, China), and were cultured at 30 °C for at least 7 days. The pure culture was obtained as described previously 24 , 25 and stored at 4 °C for further study. These pure isolates were cultivated on Columbia or LB agar at 30 °C unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acids were saponified, methylated, extracted and analysed following the midi technical note [27] with an Agilent 7890A instrument with the midi System (Sherlock version 6.1; database TSBA6). Polar lipids were extracted with chloroform–methanol and analysed by two-dimensional TLC described by Wang et al [28]. Menaquinone was prepared and analysed by HPLC (Agilent 1260) following the method described by Tamaoka [29].…”
Section: Phenotype Physiology and Chemotaxonomymentioning
confidence: 99%
“…Anaerobic growth was assessed in the anaerobic glovebox at 30 °C for 3 days. Catalase activity and oxidase activity were tested using the methods described by Wang et al [44]. Additionally, other physiological properties were test using API 20NE, API 50CHB and API ZYM systems (bioMérieux).…”
Section: Physiology and Chemotaxonomymentioning
confidence: 99%